Istimna’ Bi Yadin Nafsi Bagi Pasangan Long Distance Marriage (LDM) Menurut Ulama Kota Medan - Prayoga, M. Kevin; Mukhsin, Abdul (IAI Darussalam, 2024)
The aim of this research is to find out the law of carrying out istimna’ bi yadin nafsi (masturbating with one’s own hands) for long distance marriage couples according to Islamic law, and to find out how to maintain harmony in LDM couples according to Islamic law. This research is a qualitative research type of empirical juridical research, using two primary and secondary data sources. The primary data source comes from interviews with functionaries of the Indonesian Ulema Council (MUI) Medan City, and secondary data comes from books and literature related to research topic. The results of this research show that the law of carrying out istimna’ bi yadin nafsi for long distance marriage (LDM) couples in Islam is a complex issue among ulama. In the rules of fiqh, the principle “a real benefit must take precedence over mafsadah that is not yet real” is applied. Some Ulama in the city of Medan allow istimna’ yadin nafsi (masturbating with one’s own hands) for couples undergoing long distance marriages, with conditions and approval from both, and some other Ulama do not allow this practice because they hold the view that it is better to maintain chastity. And avoiding actions that could have a negative impact on the relationship.